(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article provides general information about the concept of the pedagogical image of a pedagogue in the conditions of New Uzbekistan. This includes the definition of the concept, its history and current status, and its role in improving the education system. Also, current problems faced by pedagogues in New Uzbekistan and ways to overcome them will be considered. At the end of the article, the pedagogical image and the consequences of its improvement are analyzed in the improvement of the education system in New Uzbekistan.